Spiritual and Political Activities of Catholikos Sargis I Sevantsi - Alexanyan, Vardan (History and Culture, 2023)
The article examines the spiritual and political activities of the Armenian Catholicos Sargis I Sevantsi (992-1019) during the reign of Gagik I (990-1018), when the Bagratid kingdom was in the period of greatest power and prosperity. The Armenian Church and the Patriarch play an important role in ensuring the political unity of the country, resolving conflicts between feudal principalities and uniting the people around statehood. On the initiative of the Catholicos in 992, the spiritual center of the country was transferred from Argina to Ani, which was dictated by the need to implement a unifying mission by combining church and political resources. After the death of Gagik I Bagratuni (1018) in the context of deepening internal political tensions in the country, the aged patriarch was forced to renounce the patriarchal throne and in 1019 ordain Petros Getadardz (1019-1054) as the new head of the church.One of his important initiatives to strengthen the integrity and unity of the hierarchical structure of the Armenian Church was the restoration in 1006 of the metropolitan privileges of the highly revered throne of Syunik.At the beginning of the 11th century, he waged a consistent struggle against the Tondrakit movement, which had risen with renewed vigor in Armenia, whose ideology undermined the hierarchical and religious foundations of the Armenian Church. The Armenian patriarch waged a merciless fight against the Tondrakites, who had strengthened themselves in the provinces of Apaunik, Mananaghi and Hark.He resisted the encroachments of the Byzantine Church and defended the hierarchical and confessional independence of the Armenian Church. Thanks to the activities of Sargis Sevantsi, the authority of the Catholicosate increases and the hierarchical structure of the church is strengthened.